Using Fuzzy Analytics to Evaluate Organizational Culture Shifts in the Era of Cybernetics - Mohammad, Suleiman Ibrahim; N, Yogeesh; Al- Daoud, Khaleel; Raja, N; Sathishkumar, A; Varghese, Rosemary; Hunitie, Mohammad Faleh Ahmmad (Journal of Posthumanism, 2024)
This study explores how cybernetic principles—emphasizing feedback loops, self-regulation, and continuous adaptation—can drive shifts in organizational culture, and proposes a fuzzy analytics framework to measure and interpret these changes. Drawing on a mixed-methods case study of a medium-sized technology firm, the research integrates qualitative inputs (interviews, focus groups) with quantitative survey data to assess culture indicators such as Leadership Adaptability, Communication Openness, and Innovative Mindset. Fuzzy logic techniques capture the nuanced, in-between states of cultural phenomena by translating subjective perceptions into membership functions and applying rule-based inference to generate a Culture Shift Index (CSI). Results indicate that organizations with rapid information flow and efficient decision loop mechanisms exhibit more pronounced culture shifts, particularly in leadership responsiveness and communication patterns. However, developing a robust innovative mindset may require additional time and focused interventions. The findings illuminate the value of fuzzy analytics in handling the ambiguity and gradual nature of cultural transformations, offering a richer understanding of how cybernetic feedback loops facilitate or constrain organizational evolution. This study contributes to the theoretical discourse on adaptive organizational systems and provides a practical toolset for managers, HR professionals, and change agents seeking to foster agile and innovation-driven cultures in technologically dynamic settings. Limitations include the potential biases in qualitative responses and the context-specific membership function definitions, suggesting opportunities for future research in diverse and longitudinal scenarios.